Cardiometabolic Effects of High‐Intensity Hybrid Functional Electrical Stimulation Exercise after Spinal Cord Injury. Issue 9 (4th December 2020) - Solinsky, Ryan; Mercier, Hannah; Picard, Glen; Taylor, J. Andrew
Abstract : Introduction: The prevalence of cardiometabolic disease following spinal cord injury is known to be high. However, it is unknown whether engaging in high‐intensity exercise, which is advocated by recent guidelines, is beneficial or feasible for these individuals. Objective: To assess the effects of high‐intensity, whole‐body exercise on the prevalence of cardiometabolic disease in individuals with spinal cord injury. Design: Combination of a randomized controlled trial and an open label intervention study of functional electrical stimulation legs plus arms rowing. Setting: Outpatient academic rehabilitation hospital. Participants: Forty individuals with spinal cord injury, with American Spinal Injury Association (ASIA) impairments scales A‐D and neurological levels of injury C1‐T12. Intervention: Six months of high‐intensity, hybrid‐functional electrical stimulation rowing. Main Outcome Measures: Change in VO2max, serum lipids, and insulin resistance, prevalence of cardiometabolic disease. Results: Individuals averaged 42.1 ± 22.0 minutes of hybrid‐functional electrical stimulation rowing a week over an average of 1.69 sessions per week over the 6 months of intervention. This amounted to an average of 170.9 ± 100 km rowed, at a mean heart rate of 82.7% of individualized maximum. Only one of 40 individuals met current exercise guidelines for the full 6 months. VO2max increased significantly ( P < .001), yet prevalence of cardiometabolic disease did not change significantly (decrease from 22.5% to 20%, P = .70). Hemoglobin A1c did decrease significantly over this time ( P = .01), although serum lipids and fasting glucose/insulin levels were unchanged. In exploratory subanalyses assessing individuals injured ≤12 months, those with more chronic injuries decreased their triglyceride‐to‐high‐density lipoprotein (HDL) ratio ( P = .04), a marker of cardiac mortality. Stratifying by neurological level of injury, individuals with paraplegia had worsened low‐density lipoprotein (LDL) level ( P = .02) and total cholesterol‐to‐HDL ratio ( P = .04) over the 6‐month intervention. Conclusions: Sustained high‐intensity exercise with hybrid functional electrical stimulation rowing does not decrease the prevalence of cardiometabolic disease after spinal cord injury.